2013
DOI: 10.1017/s0033291713000780
|View full text |Cite
|
Sign up to set email alerts
|

Offspring psychopathology following preconception, prenatal and postnatal maternal bereavement stress

Abstract: Background Preconception, prenatal, and postnatal maternal stress are associated with increased offspring psychopathology, but findings are inconsistent and need replication. We estimated associations between maternal bereavement stress and offspring autism spectrum disorder (ASD), attention-deficit/hyperactivity disorder (ADHD), bipolar disorder, schizophrenia, suicide attempt, and completed suicide. Methods Using Swedish registers, we conducted the largest population-based study to date examining associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
136
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(147 citation statements)
references
References 90 publications
(221 reference statements)
10
136
1
Order By: Relevance
“…Comparing our current and previous results, we cannot ignore the possibility that analyzing death and serious illness as one exposure might have diluted the effect of exposure to death only in this cohort. However, recent studies from other Scandinavian countries have shown results similar to ours, and they identified no association between the death of a close family member during pregnancy and schizophrenia in the offspring (Abel et al, 2014;Class et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Comparing our current and previous results, we cannot ignore the possibility that analyzing death and serious illness as one exposure might have diluted the effect of exposure to death only in this cohort. However, recent studies from other Scandinavian countries have shown results similar to ours, and they identified no association between the death of a close family member during pregnancy and schizophrenia in the offspring (Abel et al, 2014;Class et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…Early life stress, such as death or serious illness of close relatives, is one such risk factor that has been hypothesized to increase the risk of schizophrenia. However, while some epidemiological studies have found associations between schizophrenia and exposure to early life stress during pregnancy (Huttunen and Niskanen, 1978;Khashan et al, 2008), others have not (Abel et al, 2014;Class et al, 2013). Varying definitions in exposure and outcome result in different estimates, and focused studies aiming to explain potential disease-causing mechanisms are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the effect of maternal stress on offspring development has been linked to an increased risk of psychopathologies, including attention deficit hyperactivity disorder (ADHD), autism spectrum disorder (ASD), major depressive disorder (MDD), schizophrenia, and drug addiction (Beversdorf et al, 2005;Pelham et al, 2007;Khashan et al, 2008;Bale et al, 2010;Franklin et al, 2010;Arnsten, 2011;Dietz et al, 2011;Kolb et al, 2012;Class et al, 2014). Although there is a well-established relationship between maternal stress and mental health, very little is known regarding the effect of preconception paternal stress (PPS) on the developing brain of offspring.…”
Section: Introductionmentioning
confidence: 99%
“…One study investigated the association between prenatal and postnatal bereavement stress; no association was found with schizophrenia; however, associations were found with some other psychiatric morbidities [16].…”
Section: Pregnancy Factorsmentioning
confidence: 99%